Dampak Intervensi Kesehtan Gigi dan Mulut Usia Lanjut di 3 Puskesmas Jakarta Selatan Tahun 1999 - Yuyus Rusiawati (Faculty of Dentistry, Universitas Indonesia, 2015)
Life expectancy rate is increasing in the future. Elderly will be more every year was predicted 2005 - 2010 will be 19 million or 8,5% (BPS, 1997). Dental oral health problems, malocclusion, communication, aesthetics, and very important, which can cause oral diseases on systemic diseases of the body due to oral focal infections. Sample : 150 respondents 55 - 65 years old, from 3 Puskesmas in South of Jakarta, 1997 - 1998, who lived in areas Puskesmas. With statistically significant (p<0,05), DMF-T before and after intervention in Puskesmas Pesanggrahan (13.8-15.0), Cilandak (11.74-14.76) and Setiabudi as Control (13.01-13.7). The results show that dental health status intervention was better than control.